Clinical Features of HIV Arthropathy in Children: A Case Series and Literature Review - Harrison, Michael J.; Brice, Nicola; Scott, Christiaan (Frontiers in Immunology, 2021)
Background HIV infection has been associated with a non-erosive inflammatory arthritis in children, although few published reports exist. This study describes the clinical, laboratory and imaging features of this noncommunicable disease in a series of HIV-infected children in South Africa. Methods A database search was conducted to identify HIV-infected children enrolled in a Paediatric Rheumatology service in Cape Town, South Africa between 1 January 2010 and 31 December 2020. Retrospective data were collected from individuals classified with HIV arthropathy, based on a predefined checklist. Demographic, clinical, laboratory, sonographic, therapeutic, and outcomes data were extracted by chart review. Descriptive statistical analysis was performed using R (v4.0.3). Results Eleven cases of HIV arthropathy were included in the analysis. Cases predominantly presented in older boys with low CD4+ counts. Median age at arthritis onset was 10.3 years (IQR 6.9 – 11.6) and the male-female ratio was 3.0. The median absolute CD4+ count was 389 cells/uL (IQR 322 – 449). The clinical presentation was variable, with both oligoarthritis and polyarthritis being common. Elevated acute phase reactants were the most consistent laboratory feature, with a median ESR of 126 mL/h (IQR 67 – 136) and median CRP of 36 mg/L (IQR 25 – 68). Ultrasonography demonstrated joint effusions and synovial hypertrophy. Response to therapy was slower than has generally been described in adults, with almost all cases requiring more than one immunosuppressive agent. Five children were discharged in established remission after discontinuing immunotherapy, however outcomes data were incomplete for the remaining six cases. Conclusions In this case series, HIV arthropathy was associated with advanced immunosuppression. Therapeutic modalities included immunomodulators and antiretroviral therapy, which consistently induced disease remission although data were limited by a high rate of attrition. Prospective studies are needed to define and understand this HIV-associated noncommunicable disease.